Technology Shocks and Aggregate Fluctuations : How Well Does the RBC Model Fit Postwar U.S. Data? - Gali Garreta, Jordi; Rabanal, Pau. (Washington, D.C. : International Monetary Fund, 2004)
Our answer: Not so well. We reached that conclusion after reviewing recent research on the role of technology as a source of economic fluctuations. The bulk of the evidence suggests a limited role for aggregate technology shocks, pointing instead to demand factors as the main force behind the strong positive comovement between output and labor input measures.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet